MAES/EUNIS habitat map Austria 10m - Umweltbundesamt (PANGAEA, 2021)
This raster data set with a cell size of 10 meters is a compilation of different data sets in order to show Austria extquotesingles biotope types. It served as a basis for the designation and identification of sensitive habitats, which are used in the evaluation of the exceedance of critical nitrogen loads. Since biotope mapping is not available in all federal states or does not cover the entire federal territory, it was necessary to consult other available information and integrate it. The classification of habitats according to EUNIS was used as a basis for the integration of the different data sets. All input data were mapped according to this classification system. Values distinguish these categories (following the EUNIS level 1 definitions): 1...parkland, 2...farmland, 3...meadows, 4...alpine pastures, 5...forests, 6...water bodies, 7...glaciers, 8...low vegetation sites, 9...built-up area.